Assisted Reproductive Technology as a Transcutaneous Route for Bacterial Contamination of Ovarian Endometrioma with Coagulase-Negative Staphylococcus: Case Report and Review of the Literature. (29th November 2019) - Edelstein, Shimon; Ben Shachar, Inbar; Ben-Amram, Hila; Biswas, Seema; Marcus, Naama
Abstract : Tubo-ovarian abscess may develop in women with endometrioma following assisted reproductive technology (ART). The infection, though rare, is typically late in onset and may present several months after the procedure, and in pregnancy—with the risks of abortion and premature labor. It is thought that transcutaneous oocyte retrieval during ART is the route for bacterial contamination resulting in infection of the endometrioma. Pathogens reported in the literature include Escherichia coli ( E. coli ) and Group B streptococcus (GBS) but Staphylococcus lugdunensis ( S. lugdunensis ), a coagulase-negative staphylococcus (CoNS), and groin and perineal skin commensal was isolated from the endometrioma in this case. We discuss the challenges in diagnosis and treatment of this rare condition and the implications of the discovery that an organism previously dismissed as a contaminant has emerged as a causative organism in severe, deep-seated infections of soft tissues in recent literature.